Chronic Obstructive Pulmonary Disease and Its Management - Shrestha, Krishna Devi (Journal of Nursing Education of Nepal, 2023)
Chronic obstructive pulmonary disease (COPD) is a highly prevalent, life-threatening lung disease worldwide. It represents a complex respiratory disorder characterized by chronic airflow limitation that interferes with normal breathing and is not fully reversible. More than 3 million people died of COPD in 2012, which accounts 6% of all global deaths. More than 90% deaths occur in low- and middle-income countries. World Health Organization predicts that it will become the third leading cause of death worldwide by 2030. The primary cause of COPD is tobacco smoking. The patients present with a variety of symptoms primarily dyspnea, chronic cough and sputum production that impact health-related quality of life. Co-morbidities associated with COPD increases morbidity and mortality. The management of COPD requires integrated care programs based on the individual assessment of the severity of the disease. Most outcomes in COPD can be modified by pharmacological, non- pharmacological and nursing interventions. Therefore, this article aims to provide information  about COPD, its causes, symptoms, co-morbidities, exacerbations and its management
Keywords: NA